PENERAPAN SISTEM KEARSIPAN UNTUK MENINGKATKAN EFISIENSI LAYANAN PUBLIK DI TINGKAT KELURAHAN - Iyam L. Dua; Silvy Truly Sambuaga; Inka M. S. Tumengkol; Lietje Lumatauw; Christien Adriani Karambut (JURNAL DAYA-MAS, 2026)
Effective archival management is a fundamental prerequisite for creating orderly, efficient, and transparent government administration at the sub-district level. This community service activity aimed to improve the archival system at Malalayang Dua Sub-District Office, Manado City, which faced significant challenges including disorganized document storage, lengthy search times averaging 15-30 minutes per document, and minimal knowledge of archival classification systems among staff. The method employed participatory training approach involving socialization, practical training, technology implementation using Google Drive, and intensive mentoring with simulation practices. The training covered three main materials: types of archives (active, inactive, and permanent), five classification systems (alphabetical, numerical, geographical, subject, and chronological), and archival retention schedule preparation. Results showed significant improvement in staff competency, with 92% of participants able to distinguish archive types and 88% capable of applying appropriate classification systems after training. Implementation of combined geographical-alphabetical classification for population archives and subject-chronological system for correspondence successfully reduced document search time to 3-5 minutes, representing an 80-83% efficiency improvement. This activity demonstrates that systematic training and appropriate classification system implementation can significantly enhance public service quality at the sub-district level